Down syndrome: characterisation of a case with partial trisomy of chromosome 21 owing to a paternal balanced translocation (15;21) (q26;q22.1) by FISH. Issue 1 (January 1997) - Nadal, M; Moreno, S; Pritchard, M; Preciado, M A; Estivill, X; Ramos-Arroyo, M A
Abstract : A patient with a typical Down syndrome (DS) phenotype and a normal karyotype was studied by FISH. Using painting probes, we found that the patient had partial trisomy of chromosome 21 owing to an unbalanced translocation t(15;21) (q26; q22.1) of paternal origin. To correlate genotype with phenotype as accurately as possible, we localised the breakpoint using a contig of YACs from the long arm of chromosome 21 as probes and performed FISH. We ended up with two YACs, the most telomeric giving signal on the der (15) in addition to signal on the normal chromosome 21 and the most centromeric giving signal only on both normal chromosomes 21. From these results we could conclude that the breakpoint must be located within the region encompassing YACs 280B1 and 814C1, most likely near one end of either YAC or between them, since neither YAC814C1 nor 280B1 crossed the breakpoint (most likely between marker D21S304 and marker D21S302) onband 21q22.1. The same study was performed on the chromosomes of the father and of a sister and a brother of the patient; all three carried a balanced translocation between chromosomes 15 and 21 and had a normal phenotype. We also performed a prenatal study using FISH for the sister. The fetus was also a carrier of the balanced translocation.